Kesadaran Kesehatan Mental Berbasis Nilai-Nilai Islam pada Anak TKI untuk Mengatasi Dampak Parental Absence - Nurasyikin, Nurasyikin; Sa’adah, Nurus (VISA: Journal of Vision and Ideas, 2025)
In individual development, mental health must be considered, especially for children who experience parental absence. There are some children who experience parental absence, for example, children of Indonesian Migrant Workers who are separated from their parents. The phenomenon of parental absence here can have a negative impact on children's mental health, for example, children will experience emotional problems, anxiety, stress, or feelings of loneliness. This study aims to analyze mental health awareness based on Islamic values in Indonesian Migrant Workers children to overcome the impact of parental absence. The research method used in this writing adopts a qualitative research method. The findings of the study are that in overcoming the impact of parental absence on Indonesian Migrant Workers children can be applied through Islamic values. The application of these Islamic values aims to maintain the mental health of Indonesian Migrant Workers children due to parental absence. There are several Islamic values that can be implemented for Indonesian Migrant Workers children in overcoming the impact of parental absence, including tawakkal, moral and ethical education, prayer and worship, gratitude, and patience. Mental health education provided to children of migrant workers through an Islamic-based approach not only strengthens children's mental resilience, but can also provide spiritual support, so that the hope is that children's growth and development can run well even though they are faced with various life challenges.